Electrospinning of Poly[acrylonitrile‐co‐(glycidyl methacrylate)] Nanofibrous Mats for the Immobilization of Candida Antarctica Lipase B - Dai, Tianhe; Miletic, Nemanja; Loos, Katja; Elbahri, Mady; Abetz, Volker (Macromolecular Chemistry and Physics, 2010)
PANGMA nanofibers and nanomats with fiber diameters of 200–300 nanometers were fabricated by electrospinning. Cal-B was covalently immobilized onto the PANGMA nanomats via three different immobilization routes. The properties of the Cal-B-immobilized PANGMA nanomats were assayed and compared with the free Cal-B. The observed Cal-B loading on these nanomats is up to 50mg/g, and their hydrolytic activity is up to 2 500 nmol/min/mg, much higher than free enzyme powder and also slightly higher than Novozyme 435. Cal-B immobilized PANGMA nanomats have better reusability, thermal stability, and storage ability than free Cal-B. They retain over 50% of their initial activity after 15 cycles, over 65% after 10 h heat incubation, and over 75% after 30 d storage. Published